PENGARUH TERPAAN MEDIA IKLAN POLITIK TERHADAP PERILAKU PEMILIH PEMULA - undang suryatna (Universitas Djuanda Bogor, 2011)
This research aimed at analyzing the effects of political advertising media exposure, political advertising message, and message and political advertising media exposure on the beginner voter behaviors. This research had been designed in a correlation survey research and had been conducted at Kabupaten Sukabumi. Research population consisted of the beginner voter of students in high school of SMAN 1 Parungkuda in Regent and Vice Regent Election at Sukabumi District in 2010, and 121 students were determined as the research samples with a simple random sampling method. The collected data were analyzed with Pearson’s product moment correlation and multiple regression analysis. Result of the research showed that the voting behaviors of the beginner voter were significantly affected (P<0.05) by the advertising media exposure, the political advertising media message, and both the political advertising media exposure and advertising media messages